Kiswahili Poetry and Its Role in Preservation of the History of Struggle for Freedom in Africa - Kinoti, Timothy M.; Kobia, John M.; Mukuthuria, Mwenda (My University, 2015)
This research investigated the portrayal of the African politician in Kiswahili poetry. Basically, this research intended to shed light on how different poets have portrayed African politicians creatively with a purpose of revealing how these leaders have changed since colonial times to the multi-party period. The research assumed that political leaders played a great role in the development of their individual countries and Africa as a whole. The attainment of various developmental goals such as Kenya’s Vision 2030 and strengthening of the East African Community is to a large extent pegged on political decisions. The objectives of this research were to investigate the role of Kiswahili poetry in preserving the history of the African politician and to examine the traits of the pre-colonial and post-colonial African politician according to Kiswahili poets. The researcher assumed that the poet speaks for the citizen who gets adversely affected by decisions and actions taken by politicians. The study was guided by Romanticism theory developed by William Wordsworth and Samuel Taylor Coleridge and Post-colonial Theory which is associated with the works of Edward W. Said, Gayatri Chakravorty Spivak and Homi K. Bhabha. The study was carried out in the library where purposive sampling method was used to collect data from selected anthologies. Qualitative analysis of the selected poems was done guided by the research objectives. The findings of this study revealed that Kiswahili poetry is an important tool for preserving the history of Africa’s struggle for independence. The study also revealed how the seemingly royal pre-independence African politician changed drastically after independence was attained and became a tormentor of the very people he had sworn to protect. Despite these shortcomings, it is evident that the African continent has a few political role models whom the current and future politicians can emulate. The findings of this research will benefit Kiswahili scholars, writers and all political stakeholders in Africa and beyond.
Keywords: African politician; Kiswahili poetry; poetic character